Формирование выхлопного отсека перспективного ЦНД с рабочей лопаткой 1650 мм - Солодов, Валерий Григорьевич; Конев, Владимир Афанасьевич (НТУ "ХПИ", 2018)
Рассмотрены результаты расчетно-конструкторских разработок и численных исследований проточной части выхлопного отсека цилиндра низкого давления (ЦНД) в составе последней ступени с рабочей лопаткой 1650 мм с отсосом влагоемкого пара из межвенцового зазора, канала предвкюченного межступенчатого зазора с отбором пара, выхлопного патрубка с учетом установки системы охлаждения и переходного патрубка. Представлены некоторые методические аспекты и сравнительные результаты исследований на основе численного эксперимента.

The results of computational design and numerical studies of the low-pressure cylinder exhaust chamber flow path with the last stage with a 1650 mm length blade are considered. The flow path of stage contained a suction of a moisture-intensive vapor from the interrow gap, a channel of the predetermined interstage gap with steam extraction, an exhaust pipe, taking into account the installation of the system cooling and transition nozzle. All the computations were based on the model of one speed wet steam flow without droplets and super cooling was not taken into account. The sectorial approach was applied to description of the interaction of the last stage and exhaust hood. The stages were considered in steady state formulation. The initial data and boundary conditions were taken basing on results of flow simulation of whole L.P.C flow path [1, 2]. Some methodological aspects and the directions of improving of studied facilities in numerical experiment by MTFS® code are discussed.
Formation of prospective L.P.C. exhaust compartment with the 1650 mm blade length
Keywords: цилиндр низкого давления; выхлопной отсек; диффузор; ступени; утечки пара; проточная часть; потери кинетической энергии; неравномерность давления; численная модель; low-pressure cylinder; exhaust compartment; flow path; stages; diffuser; steam leakage; flow section; kinetic energy loss; pressure nonuniformity; numerical model